The Influence of ITZY Brand Ambassador on The Purchase Intention of Ultra Milk Products Through Brand Image as a Mediating Variable - Idris, Auliya Arasy'difah; Andharani, Sri Nastiti; Fiandari, Yulist Rima (Universitas Muhammadiyah Malang, 2024)
This study aims to determine the influence of brand ambassadors on purchase intention. Determine the influence of brand ambassadors on purchase intention. Determine the effect of brand image on purchase intention. Knowing the role of mediating brand image on the relationship between brand ambassadors and purchasing intention. This study uses a quantitative method with a descriptive approach. The analytical method used is path analysis using SPSS 25. This study used 110 respondents using non-probability sampling with a purposive sampling approach. From this research, the results obtained from brand ambassadors have a significant positive effect on purchase intention. Brand ambassadors have a significant positive effect on brand image. Brand image has a significant positive effect on purchase intention. Brand image mediates the relationship between brand ambassadors and purchase intention.